Optical transmittance of 2D macroporous silicon structures - Karachevtseva, L.A.; Lytvynenko, O.O.; Malovichko, E.O.; Stronska, O.J.; Busaneva, E.V.; Gorchinsky, O.D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
Optical transmittance by 2D macroporous silicon structures was investigated in direction parallel to pores. Absolute photonic band gap was measured for wavelengths between one and two optical periods of macroporous silicon structure. For wavelengths less than optical period of macropores there are an essential reduction in transmittance of electromagnetic radiation to (3-6)•10⁻³ apparently the homogeneous material and the step formation. Transmission spectra of macroporous silicon as well as steps were explained by a model of directed and decay optical modes formed by macroporous silicon as a short wave-guide structure with a large contrast in dielectric constants of the macropore and the silicon matrix.